2022
DOI: 10.1016/j.ecresq.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in maternal and child mental health responses to the COVID-19 pandemic

Abstract: We used latent profile analysis on a longitudinal dataset to examine changes in maternal and child mental health during COVID-19 and factors that may protect against declines in mental health. Participants were 183 low-income mothers ( M = 36 years) with young children ( M = 5.31 years) in the City of Toronto with data collected prior to and during the pandemic in 2020. Mothers reported on their own stress, anxiety and depression and their children's emotional, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
(100 reference statements)
0
15
1
2
Order By: Relevance
“…A study conducted by Calarco et al ( 2020 ) in the US found that mothers who assumed greater childcare responsibilities reported greater levels stress and anxiety. The literature on the psychological impacts of COVID-19, however, also revelated that not everyone was affected the same way (Hamza et al, 2020 ; Saleem et al, 2021 ). For instance, a study conducted by (Saleem et al, 2021 ) found that select groups of mothers and children did not see this expected decline in mental health, but instead experienced either stability or improvement in their mental health following the onset of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Calarco et al ( 2020 ) in the US found that mothers who assumed greater childcare responsibilities reported greater levels stress and anxiety. The literature on the psychological impacts of COVID-19, however, also revelated that not everyone was affected the same way (Hamza et al, 2020 ; Saleem et al, 2021 ). For instance, a study conducted by (Saleem et al, 2021 ) found that select groups of mothers and children did not see this expected decline in mental health, but instead experienced either stability or improvement in their mental health following the onset of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Selama penutupan sekolah terkait COVID-19 dimana anak-anak sering tiggal dirumah (S. J. Lee, Ward, Chang, & Downing, 2021) dan berinteraksi dengan anggota keluarga termasuk lansia (Saleem, Burns, Falenchuk, Varmuza, & Perlman, 2022), sedangkan di lingkungan rumah sangat sulit diterapkan socil distancing terhadap salah satu anggota keluarga yang terpapar covid karena mengganggu aktivitas sehari-hari terutama bagia anak-anak yang dalam fase bermain(J. Lee, 2020).…”
Section: Pendahuluanunclassified
“…Several studies show large declines in mental health after the pandemic onset. In a cohort of low-income mothers in Toronto, 83% reported decreases in at least one indicator of mental health between the data collection wave prior to the pandemic and during the pandemic (May–November 2020) (Saleem et al 2022 ). A large study in the UK found clinically relevant depressive symptoms in mothers increased from 11% prior to the pandemic (January 2016–March 2020) to 20% during the pandemic (March–June 2020) and anxious symptoms increased from 10 to 16% (Dickerson et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few large studies have focused on mental health of mothers during the pandemic, and those that do are mostly cross-sectional or have a brief length of follow-up. Although there have been many longitudinal COVID-19 mental health studies (COVID-Minds Network 2021 ; Unnarsdóttir et al 2021 ), few focus on maternal mental health; all take place in Canada, Denmark, and the UK; and none specifically assess PPD history (Dickerson et al 2022 ; Ladekarl et al 2021 ; Overbeck et al 2022 ; Racine et al 2022 ; Saleem et al 2022 ; Zhang et al 2022 ). Only one Danish cohort examines symptom trajectories at multiple timepoints throughout the pandemic, and they found no differences (Overbeck et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%